PENDAPATAN DAN TATANIAGA USAHATANI TANAMAN HIAS DI DESA PETIGA KECAMATAN MARGA KABUPATEN TABANAN - Made Karwan Kusniadi; I Made Tamba; I Made Suryana (AGRIMETA : Jurnal Pertanian Berbasis Keseimbangan Ekosistem, 2018)
This research aims to analyze the income and describe the ornamental plants trading system farmers production in the Petiga Village. Determination of research location is conducted by purposive with base of consideration that Petiga Village is village of ornamental plant production center in Tabanan. The respondent collected using simple random sampling method as much as 41 people and snowball sampling method as much as 3 people.From the results of the study concluded that the average income of ornamental farmers on month of Rp. 2,464,242.6 with R / C ratio of 1.57 and there are 4 channels of ornamental plants trading where the largest distribution volume is found in channel 4 by absorbing 50% of farmers' and farmer's share's largest production in channel 1 of 100%.